Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's solve the two parts of this problem step by step:
### Part (a)
Expand [tex]\((\alpha \beta + \beta \gamma + \gamma \alpha)^2\)[/tex]:
We will use the formula for squaring a sum of three terms:
[tex]\[ (a + b + c)^2 = a^2 + b^2 + c^2 + 2ab + 2bc + 2ca \][/tex]
Here, let:
[tex]\(a = \alpha \beta\)[/tex]
[tex]\(b = \beta \gamma\)[/tex]
[tex]\(c = \gamma \alpha\)[/tex]
Then,
[tex]\[ (\alpha \beta + \beta \gamma + \gamma \alpha)^2 = (\alpha \beta)^2 + (\beta \gamma)^2 + (\gamma \alpha)^2 + 2(\alpha \beta)(\beta \gamma) + 2(\beta \gamma)(\gamma \alpha) + 2(\gamma \alpha)(\alpha \beta) \][/tex]
Now calculate each term:
[tex]\[ (\alpha \beta)^2 = \alpha^2 \beta^2 \][/tex]
[tex]\[ (\beta \gamma)^2 = \beta^2 \gamma^2 \][/tex]
[tex]\[ (\gamma \alpha)^2 = \gamma^2 \alpha^2 \][/tex]
[tex]\[ 2(\alpha \beta)(\beta \gamma) = 2 \alpha \beta^2 \gamma \][/tex]
[tex]\[ 2(\beta \gamma)(\gamma \alpha) = 2 \beta \gamma^2 \alpha \][/tex]
[tex]\[ 2(\gamma \alpha)(\alpha \beta) = 2 \gamma \alpha^2 \beta \][/tex]
So, when combined, we get:
[tex]\[ (\alpha \beta + \beta \gamma + \gamma \alpha)^2 = \alpha^2 \beta^2 + \beta^2 \gamma^2 + \gamma^2 \alpha^2 + 2 \alpha \beta^2 \gamma + 2 \beta \gamma^2 \alpha + 2 \gamma \alpha^2 \beta \][/tex]
### Part (b)
If [tex]\(\alpha, \beta, \gamma\)[/tex] are the roots of the equation [tex]\(x^3 - x^2 + 2x + 6 = 0\)[/tex], we need to find a cubic equation with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex].
First, we recall Vieta's formulas for the roots of the polynomial [tex]\(x^3 - x^2 + 2x + 6 = 0\)[/tex]:
- Sum of the roots, [tex]\(\alpha + \beta + \gamma = 1\)[/tex]
- Sum of the product of the roots taken two at a time, [tex]\(\alpha \beta + \beta \gamma + \gamma \alpha = 2\)[/tex]
- Product of the roots, [tex]\(\alpha \beta \gamma = -6\)[/tex]
We want to find the polynomial with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex]. Using the relations for new roots, we find:
1. The sum of the new roots ([tex]\(\alpha^2 + \beta^2 + \gamma^2\)[/tex]):
[tex]\[ \alpha^2 + \beta^2 + \gamma^2 = (\alpha + \beta + \gamma)^2 - 2(\alpha \beta + \beta \gamma + \gamma \alpha) = 1^2 - 2 \cdot 2 = 1 - 4 = -3 \][/tex]
2. The sum of the product of the new roots taken two at a time ([tex]\(\alpha^2 \beta^2 + \beta^2 \gamma^2 + \gamma^2 \alpha^2\)[/tex]):
[tex]\[ \alpha^2 \beta^2 + \beta^2 \gamma^2 + \gamma^2 \alpha^2 = (\alpha \beta + \beta \gamma + \gamma \alpha)^2 - 2(\alpha \beta \gamma)(\alpha + \beta + \gamma) \][/tex]
[tex]\[ = 2^2 - 2(-6)(1) = 4 + 12 = 16 \][/tex]
3. The product of the new roots ([tex]\(\alpha^2 \beta^2 \gamma^2\)[/tex]):
[tex]\[ (\alpha \beta \gamma)^2 = (-6)^2 = 36 \][/tex]
So, the polynomial with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex] is:
[tex]\[ x^3 - (\text{sum of roots})x^2 + (\text{sum of products of roots taken two at a time})x - (\text{product of roots}) = 0 \][/tex]
[tex]\[ x^3 - (-3)x^2 + 16x - 36 = 0 \][/tex]
[tex]\[ x^3 + 3x^2 + 16x - 36 = 0 \][/tex]
Therefore, the cubic equation with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex] is:
[tex]\[ \boxed{x^3 + 3x^2 + 16x - 36 = 0} \][/tex]
### Part (a)
Expand [tex]\((\alpha \beta + \beta \gamma + \gamma \alpha)^2\)[/tex]:
We will use the formula for squaring a sum of three terms:
[tex]\[ (a + b + c)^2 = a^2 + b^2 + c^2 + 2ab + 2bc + 2ca \][/tex]
Here, let:
[tex]\(a = \alpha \beta\)[/tex]
[tex]\(b = \beta \gamma\)[/tex]
[tex]\(c = \gamma \alpha\)[/tex]
Then,
[tex]\[ (\alpha \beta + \beta \gamma + \gamma \alpha)^2 = (\alpha \beta)^2 + (\beta \gamma)^2 + (\gamma \alpha)^2 + 2(\alpha \beta)(\beta \gamma) + 2(\beta \gamma)(\gamma \alpha) + 2(\gamma \alpha)(\alpha \beta) \][/tex]
Now calculate each term:
[tex]\[ (\alpha \beta)^2 = \alpha^2 \beta^2 \][/tex]
[tex]\[ (\beta \gamma)^2 = \beta^2 \gamma^2 \][/tex]
[tex]\[ (\gamma \alpha)^2 = \gamma^2 \alpha^2 \][/tex]
[tex]\[ 2(\alpha \beta)(\beta \gamma) = 2 \alpha \beta^2 \gamma \][/tex]
[tex]\[ 2(\beta \gamma)(\gamma \alpha) = 2 \beta \gamma^2 \alpha \][/tex]
[tex]\[ 2(\gamma \alpha)(\alpha \beta) = 2 \gamma \alpha^2 \beta \][/tex]
So, when combined, we get:
[tex]\[ (\alpha \beta + \beta \gamma + \gamma \alpha)^2 = \alpha^2 \beta^2 + \beta^2 \gamma^2 + \gamma^2 \alpha^2 + 2 \alpha \beta^2 \gamma + 2 \beta \gamma^2 \alpha + 2 \gamma \alpha^2 \beta \][/tex]
### Part (b)
If [tex]\(\alpha, \beta, \gamma\)[/tex] are the roots of the equation [tex]\(x^3 - x^2 + 2x + 6 = 0\)[/tex], we need to find a cubic equation with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex].
First, we recall Vieta's formulas for the roots of the polynomial [tex]\(x^3 - x^2 + 2x + 6 = 0\)[/tex]:
- Sum of the roots, [tex]\(\alpha + \beta + \gamma = 1\)[/tex]
- Sum of the product of the roots taken two at a time, [tex]\(\alpha \beta + \beta \gamma + \gamma \alpha = 2\)[/tex]
- Product of the roots, [tex]\(\alpha \beta \gamma = -6\)[/tex]
We want to find the polynomial with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex]. Using the relations for new roots, we find:
1. The sum of the new roots ([tex]\(\alpha^2 + \beta^2 + \gamma^2\)[/tex]):
[tex]\[ \alpha^2 + \beta^2 + \gamma^2 = (\alpha + \beta + \gamma)^2 - 2(\alpha \beta + \beta \gamma + \gamma \alpha) = 1^2 - 2 \cdot 2 = 1 - 4 = -3 \][/tex]
2. The sum of the product of the new roots taken two at a time ([tex]\(\alpha^2 \beta^2 + \beta^2 \gamma^2 + \gamma^2 \alpha^2\)[/tex]):
[tex]\[ \alpha^2 \beta^2 + \beta^2 \gamma^2 + \gamma^2 \alpha^2 = (\alpha \beta + \beta \gamma + \gamma \alpha)^2 - 2(\alpha \beta \gamma)(\alpha + \beta + \gamma) \][/tex]
[tex]\[ = 2^2 - 2(-6)(1) = 4 + 12 = 16 \][/tex]
3. The product of the new roots ([tex]\(\alpha^2 \beta^2 \gamma^2\)[/tex]):
[tex]\[ (\alpha \beta \gamma)^2 = (-6)^2 = 36 \][/tex]
So, the polynomial with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex] is:
[tex]\[ x^3 - (\text{sum of roots})x^2 + (\text{sum of products of roots taken two at a time})x - (\text{product of roots}) = 0 \][/tex]
[tex]\[ x^3 - (-3)x^2 + 16x - 36 = 0 \][/tex]
[tex]\[ x^3 + 3x^2 + 16x - 36 = 0 \][/tex]
Therefore, the cubic equation with roots [tex]\(\alpha^2, \beta^2, \gamma^2\)[/tex] is:
[tex]\[ \boxed{x^3 + 3x^2 + 16x - 36 = 0} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.